ACTIVITIES OF STUDENT-PRODUCTION BRIGADES AND SCHOOL FORESTRIES IN RURAL SCHOOLS OF KYRGYZSTAN (FROM THE EXPERIENCE OF THE 1970S) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the activities of student production teams and school forestries in the system of labor training and education in rural secondary schools of Kyrgyzstan in the 1970s. Due to various reasons and circumstances, the named forms of labor training and education were the most popular and widespread in our republic. Their experience shows that through the activities of such forms of organizing labor training, it is possible to help the professional orientation of school children, promote the discovery of their abilities and instill a love for work, land, countryside, and homeland. The experience of such forms of labor training and education is still very useful today and has not lost its relevance.
Keywords: Labor, labor training and education, apprentice production teams, school forestries, agrotechnical knowledge, crops, seedlings, Tien Shan spruce, medicinal herbs, principles of labor training and education